Fuzzy Multiple Objective Programming in Interval Piecewise Regression Model - Tzeng, Gwo-Hshiung; Huang, Jih-Jeng (Fuzzy Multiple Objective Decision Making, 2014)
Three shortcomings associated with the fuzzy regression model have been observed (Yu et al., 2005). First, in possibility analysis, Tanaka’s methodologies were extremely sensitive to outliers or high variabilities of data and they also ignored certain information contained in the data (Kim et al., 1996; Tedden and Woodal, 1994). Second, in necessity analysis, the necessity area cannot be obtained due to large variations in the data or an inappropriate model (Tanaka et al., 1989; Tanaka and Ishibuchi, 1992).